A randomized controlled trial comparing repeated ultrasound guided aspiration versus suction catheter drainage in breast abscess - Kataria, Ruby; Singh, Saumya; Ahmad, Faraz; Kumar, Surender; Parihar, Anit (International Surgery Journal, 2019)
Background: Among different comorbidities in lactating women, breast abscess is most dreaded and common. It is more prevalent in developing world, etiology implicated to malnutrition, poor hygiene and health conditions. In era of technical advances management of breast abscess has shifted to minimally invasive and painless techniques which are more patient friendly. Methods: Hospital based randomized controlled trial was conducted at Department of Surgery, and Department of Radiodiagnosis, King Georges Medical University, Lucknow UP. Results: In our study total 80 patients were analysed, 40 randomized into USG guided needle aspiration group and other 40 into suction catheter placement group. Incidence of breast abscess was higher in lactating group and most common organism was Staphylococcus aureus. It was found that majority of women in both groups were lactating and mean age was 30 years. Same degree of fever was experienced in lactating group as in non-lactating. Amount of pain and scar volume was significantly higher in USG guided needle aspiration group. Conclusions: It seems that two treatment modalities have same effect in terms of fever and residual volume but pain and scar volume was significantly higher in group with USG guided needle aspiraton.